2019
DOI: 10.1158/0008-5472.can-18-3107
|View full text |Cite
|
Sign up to set email alerts
|

Eomes+T-betlow CD8+ T Cells Are Functionally Impaired and Are Associated with Poor Clinical Outcome in Patients with Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is a devastating blood cancer with poor prognosis. Immunotherapy targeting inhibitory pathways to unleash the antileukemia T-cell response is a promising strategy for the treatment of leukemia, but we must first understand the underlying molecular mechanisms. Eomesodermin (Eomes) and T-bet are both T-box transcription factors that regulate CD8 þ T-cell responses in a context-specific manner. Here, we examined the role of these transcription factors in CD8 þ T-cell immunity in AML p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…The experiment protocol was described in our previous published studies [47]. Briefly, purified CD8 T cells derived from PBMCs of AML patients were co-cultured with T2 cells that were pulsed with 10 μM WT1 126–134 peptide, in the presence of 50 IU IL-2 (R&D system) for 6 days.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment protocol was described in our previous published studies [47]. Briefly, purified CD8 T cells derived from PBMCs of AML patients were co-cultured with T2 cells that were pulsed with 10 μM WT1 126–134 peptide, in the presence of 50 IU IL-2 (R&D system) for 6 days.…”
Section: Methodsmentioning
confidence: 99%
“…As a master regulator of CD8 + effector and memory T cells, EOMES is critical for T-cell-mediated immune responses against pathogens [4,[6][7][8]. An accumulation of EOMES-expressing CD8 + T cells that show characteristics of exhausted cells was observed in several tumor entities [9][10][11][12]. T-cell exhaustion was first described in chronic viral infections as a dysfunctional state of CD8 + T cells that develops due to persistent antigen exposure and is characterized by the coexpression of multiple inhibitory receptors, including programmed cell death 1 (PD-1), lymphocyte activating gene 3 (LAG3), T-cell immunoreceptor with Ig and ITIM domains (TIGIT), and cluster of differentiation 244 (CD244), defective effector function, and an altered transcriptional and epigenetic state [9,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…1 A,B). Recent studies have shown that low expression levels of T-bet and high expression levels of Eomes are associated with functionally impaired CD8 + T cells 14 , 15 . In line with these findings, EV10-specific CD8 + T cells primed in the presence of TLR9L exhibited lower T-bet/Eomes ratios compared with EV10-specific CD8 + T cells primed in the presence of TLR8L or 2′3′-cGAMP (Fig.…”
Section: Resultsmentioning
confidence: 99%